Active design and its principles in industrial product design (Al-Academy, 2023)
The problem of the research came through the following question (what is the effectiveness of active design in contemporary industrial products), and it emphasized the importance of research to make society with its members in a positive state of activity, and what can help the industrial product design to achieve this, but the goal of the study is (determining the characteristics and principles of design Active and its effectiveness in the industrial product), and the study was determined by industrial products related to daily, recreational and sports activity, The researcher relied on a form to determine the axes of analysis for the sample models, in order to reach the results of the research, the most important of which are: Realize the principles of active design by finding structural and organizational features and adapting to the context of use.